(untitled) - Phillips, Deborah ([New York], 2004)
This set of Cassettes gives students all the tools they need to succeed on the TOEFL paper-based test. Providing both a comprehensive language skills course and a wealth of practice for all sections of the paper test, the Longman Preparation Course is appropriate for courses in TOEFL? test preparation or as a supplement to more general ESL courses. The cassettes have an additional 1,450 test questions in both practice sections and three more simulated tests, Pop-up explanations to enhance understanding. Easy-to-use scoring and record keeping to monitor progress.
Keywords: Test of English as a foreign language,English language